Nanoporous titanium implant surface promotes osteogenesis by suppressing osteoclastogenesis via integrin β1/FAKpY397/MAPK pathway - Yide He (KeAi Communications Co., Ltd., 2022)
Macrophages and osteoclasts are both derived from monocyte/macrophage lineage, which plays as the osteoclastic part of bone metabolism. Although they are regulated by bone implant surface nanoarchitecture and involved in osseointegration, the beneath mechanism has not been simultaneously analyzed in a given surface model and their communication with osteoblasts is also blurring. Here, the effect of implant surface topography on monocyte/macrophage lineage osteoclastogenesis and the subsequent effect on osteogenesis are systematically investigated. The nanoporous surface is fabricated on titanium implant by etching and anodizing to get the nanotubes structure. The early bone formation around implant is significantly accelerated by the nanoporous surface in vivo. Meanwhile, the macrophage recruitment and osteoclast formation are increased and decreased respectively. Mechanistically, the integrin mediated FAK phosphorylation and its downstream MAPK pathway (p-p38) are significantly downregulated by the nanoporous surface, which account for the inhibition of osteoclastogenesis. In addition, the nanoporous surface can alleviate the inhibition of osteoclasts on osteogenesis by changing the secretion of clastokines, and accelerate bone regeneration by macrophage cytokine profiles. In conclusion, these data indicate that physical topography of implant surface is a critical factor modulating monocyte/macrophage lineage commitment, which provides theoretical guidance and mechanism basis for promoting osseointegration by coupling the osteogenesis and osteoclastogenesis.